A new speech discrimination test in Tamil - Jesudas Dayalan Samuel (Journal of All India Institute of Speech and Hearing, 1970)
Speech audiomttry is an indispensable clinical tool of audiological evaluation.~,;·tts assistance in measurifhgJ hea;ing acuity, determining the anatomIc location' of the hearin; disord~r and in ,evall:lation of ability' to comlnunicate is' well known. Non-availability ofproperly prep~~ed ,' sp~ech materials in particuiar Indian la~guag~s is a well kno~v'n faci~